2023
DOI: 10.3390/pharmaceutics15030737
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for the Fabrication of 3D-Printed Dental Membrane Scaffolds including Antimicrobial Pomegranate Extract

Abstract: In this study, a dental membrane scaffold was fabricated using a 3D printing technique, and the antimicrobial effect of pomegranate seed and peel extract were investigated. For the production of the dental membrane scaffold, a combination of polyvinyl alcohol, starch, and pomegranate seed and peel extracts was used. The aim of the scaffold was to cover the damaged area and aid in the healing process. This can be achieved due to the high antimicrobial and antioxidant content of pomegranate seed and peel extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…These T g and T m temperatures changed from 65 °C to 69 °C and 262 °C-267 °C respectively, when the PEO concentration was highest in the scaffold. This result proves the energetic interactions and intermolecular connections between pure SA and PEO according to changes in the melting temperature (Ozturk et al, 2022;Karabulut et al, 2023).…”
Section: Resultssupporting
confidence: 69%
“…These T g and T m temperatures changed from 65 °C to 69 °C and 262 °C-267 °C respectively, when the PEO concentration was highest in the scaffold. This result proves the energetic interactions and intermolecular connections between pure SA and PEO according to changes in the melting temperature (Ozturk et al, 2022;Karabulut et al, 2023).…”
Section: Resultssupporting
confidence: 69%
“…One such composite scaffold synthesized from bacterial cellulose, chitosan, and hydroxyapatite was studied for the release of pomegranate peel extract. The study found that the release of the extract was dose-dependent and had a microbicidal effect with good wound-healing abilities [21,22]. However, the precise control of concentration and its cost in fabrication, and interfacial bonding is still a problem.…”
Section: Figure 5: a And B Show The Attachment Of Human Periodontal L...mentioning
confidence: 99%
“…This scaffold covers the damaged area and contributes to healing. The incorporation of PSE and PPE enhances bacteriostatic activity against S. aureus and Enterococcus faecalis , thereby improving anti-microbial efficacy and demonstrating promising potential for clinical applications ( Karabulut et al, 2023 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%